Vacuum ultraviolet gain measurements in optically pumped LiYF4:Nd3+ - Cashmore, J; Hooker, S; Webb, C (1997)
We present measurements of the net-induced gain on the 5d-4f transition at 186 nm in LiYF4:Nd3+ optically pumped by radiation from a molecular fluorine laser. It is found that for LiYF4: Nd3+ one of a series of potential continuously tunable VUV lasers, relatively strong excited-state absorption results in net-induced loss. The prospects for VUV laser operation being realised in other rare-earth-doped fluorides is discussed.